2020
DOI: 10.1186/s12879-020-05402-y
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial profile, antibiotic susceptibility pattern and associated risk factors of urinary tract infection among clinically suspected children attending at Felege-Hiwot comprehensive and specialized hospital, Northwest Ethiopia. A prospective study

Abstract: Background Urinary tract infection is one of the most common bacterial infections in children. Understanding the characteristics of uropathogens and their antimicrobial susceptibility pattern in a particular setting can provide evidence for the appropriate management of cases. This study aimed to assess the bacterial profile of urinary tract infection, their antimicrobial susceptibility pattern and associated factors among clinically suspected children attending at Felege-Hiwot Comprehensive Specialized Hospit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 33 publications
19
31
2
Order By: Relevance
“…Among the isolated gram-positive bacteria, Staphylococcus aureus represents high drug resistance. This finding is consistent with studies conducted in Saudi Arabia [36], Ethiopia [35] and Iraq [31].…”
Section: Plos Onesupporting
confidence: 93%
See 3 more Smart Citations
“…Among the isolated gram-positive bacteria, Staphylococcus aureus represents high drug resistance. This finding is consistent with studies conducted in Saudi Arabia [36], Ethiopia [35] and Iraq [31].…”
Section: Plos Onesupporting
confidence: 93%
“…According to this study, E. coli is the main urinary tract pathogen, which is consistent with almost all similar investigations [35,36,40]. This is due to the existence of many virulence factors dedicated to colonization and invasion of the urinary epithelium.…”
Section: Plos Onesupporting
confidence: 91%
See 2 more Smart Citations
“…In Iran, Behzadi et al reported that E. coli was one the most common uropathogenic bacteria causing UTI ( 16 ). In Northwest Ethiopia, among Gram-negative isolates, E. coli (63.6%) was predominant ( 17 ). Most common type of infection caused by Candida spp.…”
Section: Discussionmentioning
confidence: 99%